A transdiagnostic approach to develop organization, attention and learning skills the goals treatment manual for college students - Hansen, Laura K.; Ellis, Brandi M.; Smith, Stephanie Dunkel 1981- (New York, NY Routledge, Taylor & Francis Group, 2023)
"A Transdiagnostic Approach to Develop Organization, Attention and Learning Skills introduces the GOALS program - an innovative and skill-based approach that addresses the unique array of academic, occupational, and socio-emotional difficulties commonly faced by college students with underdeveloped executive functions. This program consists of ten sessions delivered in a group format to help college students improve their academic performance. Over the course of these sessions, participants learn strategies to prioritize tasks and assignments; schedule and manage life responsibilities; cope with life stressors; identify relevant on-campus resources; prepare for upcoming exams; take well-structured notes; maintain motivation; and several other strategies designed to reach their academic goals. Each session builds on earlier sessions, so previously learned skills lay the foundation for the successful implementation of newly learned skills. This practical and easy-to-implement program includes detailed session notes for group leaders and reproducible handouts for participants including in-session activities, session summaries, and homework assignments. This treatment manual is an essential resource for mental health providers who deliver interventions to students enrolled in post-secondary institutions pursuing undergraduate or graduate level degrees"--
Includes bibliographical references and index.
Keywords: College students -- Mental health -- Handbooks, manuals, etc; Executive functions (Neuropsychology); Organization; Study skills; Counseling in higher education -- Handbooks, manuals, etc; Attention; College students -- Mental health services -- Handbooks, manuals, etc